PENGARUH TEMAN SEBAYA TERHADAP MOTIVASI BELAJAR SISWA DALAM PEMBELAJARAN EKONOMI - Yopi Nisa Febianti; Rizkya Maulya Fani; Zahwa Nuraliza (STKIP Persada Khatulistiwa Sintang, 2026)
Interesting Economics learning can make it easier for students to understand the Economics material given, so that students do not feel bored. One way to create a conducive atmosphere when learning is by interacting with peers in class, because they can help change students' learning behavior in a positive or negative direction. This study was conducted with the aim of determining the influence of peers in the family environment (home) and at school on students' learning motivation in Economics learning. This study used a quantitative research method, namely a survey. Samples were taken from three classes with a total of 100 students. The samples in this study were students of class X IPS 1 Economics, as well as students of class X MIPA 5 and X MIPA 6 Economics Interest. The research data sources were primary and secondary data. Data analysis was carried out using the classical assumption test and the t-test. The test results showed that peers have a positive influence on students' learning motivation in Economics learning. The conclusion is that peers in this school have similarities in age and social status, and the students are smart and intelligent in class. They have an influence on learning motivation and can be used as Economics learning partners.